DEVELOPMENT OF GOOGLE SITES-BASED LEARNING MEDIA ON RETAIL BUSINESS MANAGEMENT MATERIAL - Anggraini, Wati; Faslah, Roni; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This research aims to find out the feasibility of developing Google Sites-based learning media in class XI retail business management material. This research was conducted using the research and development (R&D) method at Tamansiswa 1 Vocational High School Jakarta. The data analysis technique used is expert validation testing. Validation tests will be enforced by media experts, material experts and teachers. The media expert validation test results in stage I got a percentage of 94%, and in stage II got a percentage of 96% which can be categorized as very valid and very feasible. The material expert validation test in stage I got a percentage of 60%, and in stage II got a percentage of 82% which can be categorized as valid and feasible. The validation test by teachers obtained a percentage of 92% which can be categorized as very valid and very feasible. In small group trials conducted on 10 students, the results showed a percentage of 84.4% which was categorized as valid and feasible. The results of this research and development show that Google Sites-based learning media is declared feasible and can be used in the learning process.